Dyeing and functional properties of polyester fabric dyed with prodigiosins nanomicelles produced by microbial fermentation. (1st April 2017) - Ren, Yanfei; Gong, Jixian; Fu, Ranran; Li, Zheng; Yu, Zhicai; Lou, Jiangfei; Wang, Fubang; Zhang, Jianfei
Abstract: Nanosuspension of prodigiosins micelles produced by the fermentation of Serratia marcescens was utilized as a novel kind of cleaner disperse dye for polyester fabric dyeing. The average particle size of the pigments dispersion was 184.3 nm (range of 101.1–378.0 nm). The effects of technical parameters including dyeing temperature, dyeing time and dye bath pH on dyeing effects, antibacterial and ultraviolet protective properties of dyed fabrics were explored. The results indicated that when the dyeing temperature was set at 110 °C with a holding time of 30 min, dyed polyester under dye bath pH of 1.9 and 7.9 possessed high color strength, outstanding bacteriostatic rate of above 89.0% against Staphylococcus aureus and very good UV-protection ability. In addition, the dyed fabrics exhibited excellent rubbing, washing and perspiration color fastness but poor light color fastness. This research developed a novel clean method of preparing prodigiosins disperse dye by microbial fermentation and dyed polyester fabric to endow it with functionalities. Graphical abstract: Highlights: Prodigiosins nanomicelles are produced by the fermentation of Serratia marcescens. The clean prodigiosins disperse dye is utilized to dye polyester fabric. Prodigiosins endow polyester with good dyeing effect and functional properties. The influences of dyeing temperature, time and dye bath pH are investigated.